2006
DOI: 10.1212/01.wnl.0000203121.04509.31
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II study of the safety and efficacy of teriflunomide in multiple sclerosis with relapses

Abstract: Oral teriflunomide was effective in reducing MRI lesions and was well tolerated in patients with relapsing multiple sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
215
0
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(230 citation statements)
references
References 12 publications
4
215
0
11
Order By: Relevance
“…[2][3][4] The trials demonstrated a consistent safety and tolerability profile for teriflunomide used for 2 years. [2][3][4] A randomized trial comparing subcutaneous interferon (IFN)-b-1a with teriflunomide in relapsing MS demonstrated that efficacies of teriflunomide 14 mg and IFN-b1a were in the same range, and treatment satisfaction was greater with teriflunomide. 5 To collect long-term safety data and monitor disease activity with continued teriflunomide treatment, extension studies were established.…”
mentioning
confidence: 83%
“…[2][3][4] The trials demonstrated a consistent safety and tolerability profile for teriflunomide used for 2 years. [2][3][4] A randomized trial comparing subcutaneous interferon (IFN)-b-1a with teriflunomide in relapsing MS demonstrated that efficacies of teriflunomide 14 mg and IFN-b1a were in the same range, and treatment satisfaction was greater with teriflunomide. 5 To collect long-term safety data and monitor disease activity with continued teriflunomide treatment, extension studies were established.…”
mentioning
confidence: 83%
“…Были проведены сравнения терифлу-номида с плацебо и высокодозным бета-интерфероном-1а (βИФН-1а) [5][6][7][8][9]. В ходе нескольких многоцентровых плацебо-контролируемых международных исследова-ний II фазы была выявлена эффективность и безопас-ность препарата терифлуномид, что стало поводом для проведения дальнейших исследований.…”
Section: результаты клинических исследованийunclassified
“…76 In a 36-week study of 179 patients with RRMS or secondary progressive MS (SPMS), subjects received oral teriflunomide at either of 2 doses (7 mg or 14 mg per day) or placebo. 77 For the primary efficacy endpoint of the number of combined active unique lesions per MRI scan, significantly reduced mean numbers of lesions compared with placebo were seen in both the 7 mg (1.04 vs. 2.68, P < 0.030) and 14 mg teriflunomide groups (1.06 vs. 2.68, P < 0.010). Teriflunomide-treated patients also had significantly fewer T1-enhancing lesions per MRI scan (0.87 [7 mg ing T2-hyperintense lesions, new T1-hypointense lesions, and relapse rates.…”
mentioning
confidence: 91%